Combination of mycorrhizal fungi and phosphorus fertilization in the growth of two wild agaves - García Martínez, Ledia Itzel; Sánchez-Mendoza, Saúl; Bautista-Cruz, Angélica (REVISTA TERRA LATINOAMERICANA, 2020)
Arbuscular mycorrhizal fungi can contribute significantly to plant nutrition, especially in the phosphorus (P) assimilation. Wild agave populations are overexploited due to the intensive production of mezcal, causing the decline of natural populations. The effect of the inoculation with commercial mycorrhizal fungi and the application of different doses of P on the growth and total soluble solids content (SST) of two wild agaves: tobalá agave (Agave potatorum Zucc) and coyote agave (Agave spp.) in protected conditions was evaluated. The commercial mycorrhizal products used were Glomus cubense (M1) and Glumix (M2) and four doses of P: 0, 14.4, 29 and 43.5 mg kg-1. The assay was established into a 3 × 4 bifactorial experiment in a completely randomized design. The response variables were plant height (AP), number of leaves (NH), stem diameter (DT), root volume (VR), root density (DR), leaf fresh weight (PFH), stem fresh weight (PFT), root fresh weight (PFR) and SST. In regard to the control, M2 increased NH by 18.2%, PFH by 53.5%, PFT by 38.1% and DT by 36% in tobalá agave; whereas in coyote agave, AP increased by 12% and SST by 21.3%. In tobalá agave the dose of 43.5 mg kg-1 of P improved the AP by 13.2%, PFH by 34.9%, PFT by 36.1%, DT by 21.5% and VR by 20.4%. In coyote agave, the dose of 29 mg kg-1 of P favored the AP by 16.4%, PFT by 44.4% and DT by 18.6%. SST increased 40% with 43.5 mg kg-1 of P and the PFH increased 51% with 29 mg kg-1 of P. In tobalá agave, M2 + 43.5 mg kg-1 of P improved the PFH, PFT and DT. In coyote agave, M2 + 29 mg kg-1 of P, M2 + 14.4 mg kg-1 of P and M2 + 43.5 mg kg-1 of P promoted AP, DT and SST. The promotion of growth in both agaves was rather due to the individual application of mycorrhizal fungi and P than the interaction of both factors.